The Impact of Firm Size on Firms Performance in Nigeria: A Comparative Study of Selected Firms in the Building Industry in Nigeria - OYELADE, Aduralere Opeyemi, (Asian Development Policy Review, 2019)
The study examined the impact of firm size on firm’s performance in Nigeria: A comparative study of selected firms in the building industry in Nigeria using annual data from 2004 to 2017. The technique used in the research work was panel analysis. Based on the financial measurement of performance using both return on assets (ROA) and return on equity (ROE), two out of the four variables used as an indicators of size were statistically significant in determine return on assets which are total sales and age of firm since incorporated and total sale has positive effect on return on assets while age of firm since incorporated has a negative effect on return on assets. Furthermore, it was observed that only leverage that was significant in determine return on equity. Based on productivity measurement of performance of the selected firms in the building industry in Nigeria using both output per labour and output per capital, also two out of the four variables used as an indicators of size were statistically significant in determine output per labour which are total sales and age of firm since incorporated and both have positive effect output per labour and total number of employee and leverage has a negative significant impact on output per labour. Also, only age of firm since incorporated as a measure of size that was significant in determine output per capital out of the four measurement of size and liquidity ratio has a positive significant effect on output per capital.